Duplex sonography of paediatric peripheral vessels and soft tissue - Rupprecht, Thomas; Herterich, Reinhard; Deeg, Karl Heinz (Springer International Publishing, 2015)
Duplex Sonography of paediatric peripheral vessels and soft tissue is a heterogenous investigation area. Besides the classical clinical indications for arteriovenous (vessel) disease the indications include vascular access techniques and the investigation of soft tissue tumours. Looking at the latter the target of the chapter is the definition of a standard investigation and therapy approach.
CRIS-Team Scopus Importer:2025-03-05